2012
DOI: 10.1111/j.1439-0396.2012.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

The energy value of biodiesel glycerine products fed to broilers at different ages

Abstract: The objective of this study was to determine the apparent metabolisable energy corrected for nitrogen balance (AMEn) of some products containing glycerine from soybean oil (GOIL), a mixture of frying oil and lard (GMIX) and a semi-purified process (GSP) in broilers of different ages (10, 20, 30 and 40 days post-hatching), using two methodologies. In trial 1, the basal diets were replaced with 100 g/kg of each studied glycerine product and the diets were supplied ad libitum. Three hundred broilers were used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…For the formulation of diets, the mean values of apparent metabolizable energy corrected for the retained nitrogen (AMEn) that had been previously determined by Lima et al. () for each evaluated glycerine were utilized: 13.73 MJ AMEn/kg CGSO, 13.51 MJ AMEn/kg MCG and 13.83 MJ AMEn/kg SPGSO.…”
Section: Methodsmentioning
confidence: 99%
“…For the formulation of diets, the mean values of apparent metabolizable energy corrected for the retained nitrogen (AMEn) that had been previously determined by Lima et al. () for each evaluated glycerine were utilized: 13.73 MJ AMEn/kg CGSO, 13.51 MJ AMEn/kg MCG and 13.83 MJ AMEn/kg SPGSO.…”
Section: Methodsmentioning
confidence: 99%
“…Results from chapter 2 of the present thesis indicate that the AMEn content of glycerol close to 96% of the GE of a product containing 81-87% glycerol, less than 0.4% free fatty acids, 5% ash, 0.06% methanol and less than 10% water. This estimation is close to the predictive value of 97% of the GE obtained by Kerr et al (2011) for glycerol containing less than 0.5% free fatty acids, but higher than the range of 86.0 to 92% reported by Lima et al (2013) in products with lower glycerin and higher fat residues. Differences in the composition of the fat residue, might explain the lower values reported by these authors.…”
Section: Influence Of Glycerinsupporting
confidence: 89%
“…5 The interaction between source and level of glycerin was not significant (P > 0.10). The inclusion of up to 10% GLYC in the diet improved growth performance of the broilers with effects being more pronounced for FCR than for ADG and for the first week of life than thereafter, consistent with data of Lima et al (2013) who reported that young broilers have a higher capacity to utilize the energy content from this ingredient than older broilers. Mclea et al (2011) and Topal and Ozdogan (2013) reported also that the inclusion of 8 to 10% glycerol in the diet improved ADG and FCR in broilers from 1 to 28 d of age, in agreement with the results of the current experiment.…”
Section: Growth Performance and Digestive Trait Measurementssupporting
confidence: 87%
“…Due to the importance of glycerol in energy metabolism and its high availability due to biodiesel production, its inclusion in animal diets has generated interest. Several authors have shown that glycerine has a high energy value for poultry (Lammers et al, 2008;Dozier et al, 2011;Jung and Batal, 2011;Lima et al, 2013), regardless of compositional differences resulting from fat sources, processing methods and reagents used for biodiesel production. Lammers et al (2008), in metabolism experiments, used 48 Hy-Line W-36 laying hens, fed 0%, 5%, 10% and 15% crude glycerol in their ration and found an apparent metabolisable energy (ME) value of 15.92 MJ/kg (3805 kcal/kg).…”
Section: Introductionmentioning
confidence: 99%